The Evolution and Transformation of the Ethno-Geological Systems of the Trans-Ural Forest-Steppe into Civilized Chronotopes - Zavyalova, O G (KnE Life Sciences, 2019)
The article discusses the results of a post-dissertation doctoral study on the thousandyear evolution of the ethno-geological systems of Trans-Urals forest-steppe based on the ethno-system analysis method of territorial development and the structural ethnocontact principles developed by the author. Geographical factors of the ethno-social organization of the Russian space are an important factor of their cultural and ethnic identity and development of multi-ethnic regions. Territorial structures become trigger mechanisms of many regional processes: ethno-social, economic, environmental, etc. The resulting cooperative (synergistic) effects caused by contacts and the similar development institutions significantly influence the emerging territorial structures. Society is to be analyzed as a global ethno-system where the processes of ethnonatural interaction play a basic role. They result the evolution of territorial systems of management of natural resources and economy management. The author proposes a new content of the concept “civilization chronotope” – “Siberian” as a result of a long-term ethno-cultural transformation of the Southern Trans-Urals ethno-geosystems, ethno-contact zone, a common ethnic and economic co-evolution of the peoples of South-Western Siberia.